DNA damage induced by oridonin involves cell cycle arrest at G2/M phase in human MCF-7 cells - Zhang, Tao; Tan, Yan; Zhao, Rui; Liu, Zhaoyang (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : To study the mechanisms of inhibition of cell growth and induction of DNA damage in oridonin-treated MCF-7 human breast cancer cells. Material and methods : The cytotoxicity of oridonin-treated MCF-7 cells was measured by MTT assay. Cell cycle phase distribution was analyzed by flow cytometry. P-ATM, P-CHK2, gH2AX and P-P53 protein expressions were detected by Western blot analysis. The expression of r-h2ax and P-ATM was also detected by immunofluorescence staining. The degree of cellular damage of oridonin-induced MCF-7 human breast cancer cells was confirmed by the comet assay analysis of DNA fragmentation. Results : Oridonin inhibited cell growth in a time- and dose-dependent manner. The IC50 values at 48 and 72 hours were 78.3 and 31.62 µmol/l, respectively. Oridonin induced G2/M phase arrest in MCF-7 cells. MCF-7 cells treated with oridonin showed significant DNA damage as shown by an increase in olive tail moment (OTM). The protein expression levels of P-ATM, P-CHK2, gH2AX and P-P53 were increased significantly in a dose-dependent manner. Conclusions : DNA damage provokes p53-mediated G2/M cell cycle arrest in oridonin-induced MCF-7 cells through the mechanism of CHK2 activation by activated ATM protein kinase, which is induced by oridonin.